Validation Protocol of Vitamin D Supplementation in Patients with HIV-Infection - Elisabet Lerma-Chippirraz; Roberto Güerri-Fernández; Judit Villar García; Alicia González Mena; Ana Guelar Grinberg; María Milagro Montero; Luisa Sorli; Sonia Calzado; Juan Pablo Horcajada; Adolfo Díez-Pérez; Hernando Knobel Freud (AIDS Research and Treatment)
Hypovitaminosis D and secondary hyperparathyroidism are frequent among HIV-infected patients. As there are no data about the best supplementation therapy both in treatment and in maintenance, we conducted an observational study of 300 HIV-infected patients for whom vitamin D and parathormone (PTH) had been measured in order to validate a protocol of vitamin D supplementation in patients with HIV-infection. Patients with vitamin D deficiency (defined as 25(OH)D < 10 ng/mL), insufficiency (defined as 25(OH)D < 20 ng/mL), or hyperparathyroidism (PTH > 65 pg/mL) were supplemented with cholecalciferol 16.000IU (0.266 mg) weekly (if deficiency) or fortnightly (if insufficiency or high PTH levels). Rates of normalization of 25(OH)D (levels above 20 ng/mL) and PTH levels (<65 pg/mL) were analyzed. Multivariate analysis of factors related to normalization was carried out. With a median follow-up of 2 years, 82.1% of patients with deficiency and 83.9% of cases with insufficiency reached levels above 20 ng/mL. However, only 67.2% of individuals with hyperparathyroidism at baseline reached target levels (<65 pg/mL). Independent factors for not achieving PTH objective were tenofovir (TDF) and protease inhibitors use. In HIV-infected patients with hypovitaminosis, the protocol of cholecalciferol supplementation normalized vitamin D levels regardless of antiretroviral regimen in a high proportion of patients but it was less effective to correct hyperparathyroidism.